PEMBINAAN MOTIVASI KARIR BAGI SISWA SMA 5 MUHAMMADIYAH TAKENGON - Yanti Arnilis; Syafridha Yanti; Barep Sarinauli; Murthada; M Khoiri; Abdul Rahmad; Aqshal Arlian Raya (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2025)
Senior High School 5 Muhammadiyah Takengon is an educational institution under the Muhammadiyah organisation, which has educational institutions ranging from elementary to senior high levels. The students of SMA 5 Muhammadiyah are the future successors of the nation who need guidance and direction regarding their career and future. Many students when they graduate have a dilemma determining their direction and purpose, especially when they come from lower middle class families and parents with minimal education, of course students will experience difficulties due to the lack of knowledge from their parents or closest relatives. The planning of this activity can certainly increase awareness for students and students related to their future careers. Participants in this activity are students of class VIII IPS, where this activity is carried out for three face-to-face meetings. This activity consists of socialising the importance of education and careers and efforts to increase motivation for students. This service activity is carried out in the form of coaching. The expectation of the service team is that students' motivation and understanding of careers and their future will increase.